About the Community Leader - A Theoretical Approach - Carmen Sonia DUSE; Dan Maniu DUSE (Communications of International Proceedings, 2020)
In Romanian society there is only a pale image of the existence of community leaders, who should focus on people problems and solve them, without waiting for political involvement. Community membership is based on five attributes: boundaries, emotional security, group membership and group identification, and a common system of symbols. Community engagement can be defined in a context of partnership and reciprocity as a mutual exchange of knowledge and resources. Low community engagement leads to a lack of trust in the community. In this way, the level of unemployment, poverty and in direct connection with a poor quality education and with the increase of the crime rate are accentuated. Creating local networks of community members fosters a climate in which more people are willing to work to achieve a goal. This article is about who and what such a leader should look like, about the influence and positive changes it can bring to the community. While leaders ‘theories place great emphasis on emotional intelligence, current research speaks to culturally intelligent leaders who know and understand how culture acts on the individual, how specific values ​​and beliefs direct individuals’ behavior. At the same time, because in times of crisis we need leaders, the article shows how such a leader can coagulate energies, to overcome critical moments. The article is a theoretical study conducted as a documentary document for building a training program for community leaders.
Keywords: Community; Leader; Ethic; Influence; Culture.